2011
DOI: 10.1542/peds.2010-2427
|View full text |Cite
|
Sign up to set email alerts
|

Fish-Oil Fat Emulsion Supplementation May Reduce the Risk of Severe Retinopathy in VLBW Infants

Abstract: Fish-oil-based fat emulsion administered from the first day of life may be effective in the prophylaxis of severe retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 16 publications
3
86
0
3
Order By: Relevance
“…Eighteen of these studies were RCTs. [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among nonrandomized studies, 4 were interventional studies with a control group [30][31][32][33] and the remaining 2 studies 8,34 did not test an intervention because they examined the association of BPD with LCPUFA concentrations in blood or in tracheal aspirates. Fifteen RCTs presented dichotomous outcomes.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen of these studies were RCTs. [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among nonrandomized studies, 4 were interventional studies with a control group [30][31][32][33] and the remaining 2 studies 8,34 did not test an intervention because they examined the association of BPD with LCPUFA concentrations in blood or in tracheal aspirates. Fifteen RCTs presented dichotomous outcomes.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Several studies examined .1 neonatal outcome at a time (Table 1). Only a few studies reported other relevant neonatal outcomes, such as number of days of ventilation, or the use or duration of supplementation oxygen, 13,20,22,27,28 patent ductus arteriosus, 12,20,23,[30][31][32] cholestasis, 31,32 or number of days of hospital admission. 8,11,13,18,31,32 Effect Estimates for Dichotomous Neonatal Outcomes…”
Section: Characteristics Of Exposure and Outcomesmentioning
confidence: 99%
“…Lipid emulsions contain various amounts of medium-chain triglycerides (MCT), olive oil, and/or fish oil and are widely used in the units we surveyed, contrasting with data from France, where the most widely used lipid emulsion was soy oil (50%) + MCT oil (50%) (SO-MCT). Our study shows that Spanish neonatologists are aware of the benefits of using fish oil-based lipid emulsions for DHA status (21), retinopathy of prematurity (22), oxidative stress (23), and pulmonary hypertension (24).…”
Section: Discussionmentioning
confidence: 79%
“…Early PN is highly favorable in the prevention of IVH, the five trials that included in exploring this clinical outcome favors the early PN [27,28]. In premature infants the blood vessels are immature at birth and retina produces abnormal level of various growth factors that are important for the eye development such as Vascular Endothelial Growth Factor (VEGF) to produce more blood vessels [29][30][31].…”
Section: Discussionmentioning
confidence: 99%